Drivers that motivate participation in mangrove forest management among the local people at Barangay Lasang, Davao City, Philippines - Jadloc Johanne Astrid; Legaspina Thecil; Gabrinao Wayne Pascual; Gorgonio Charlyn (BIO Web of Conferences)
Mangrove forests, which are vital for biodiversity, climate regulation, and storm buffering, have lost half their global cover over the past century, emphasizing the essential role of local communities and indigenous peoples in their ecological management. Hence, this study aimed to generate insights and strategies to enhance local participation in mangrove forest management. This study employed a descriptive-correlational research design, and data were collected through a 100% survey of Tambongon Fisherfolks Association (TAMFIAS) members. A structured questionnaire assessed participation levels and drivers influencing mangrove forest management. Results showed a mean average participation score of 4.17, indicating frequent engagement in mangrove forest management activities. Among the drivers tested, monetary-related benefits such as the provision of financial benefits, enhanced career-related skills, and stabilized job emerged as the strongest driver (r=0.27) in mangrove forest management participation, followed by perceived ecological values (r=0.25) and ecological knowledge (r=0.24). Contrarily, nonmonetary-related benefits such as making friends, improving environmental quality, and strengthening relationships hold the weakest influence (r=0.14). The correlation between drivers that motivate participation and participation levels had a weak but positive relationship (r=0.29). Therefore, the study recommends project planners in Barangay Lasang incorporate monetary incentives during mangrove management initiatives to boost local involvement.